Support for an EU-wide social policy? A country-comparative analysis of unemployment perceptions - Hequn Wang (International Journal of Social Welfare, 2024)
Abstract This article explored the influence of unemployment perceptions on attitudes towards an EU-wide social policy that guarantees a minimum standard of living for the poor across 18 European countries. The article relied on a theoretical framework that highlights the interaction among economic self-interest, ideology, and perceptions. Using data from Eurostat and the European Social Survey, the results show that Europeans with more negative perceptions of national unemployment or the living conditions of the unemployed were more likely to support an EU minimum income scheme. This association was particularly strong among individuals with non-egalitarian values or right-leaning ideology and remained relatively consistent across different national contexts. Additionally, support was stronger in countries with poor economic and welfare conditions. Overall, the findings reveal a high perceived legitimacy among Europeans for implementing a policy measure that aims to tackle poverty in the EU.
Keywords: 330; EU social policy; minimum income; perceptions; public opinion; social Europe; unemployment